Family business foundations: Theoretical and empirical investigation - Carmela Schillaci; Marco Romano; Melita Nicotra (Journal of Innovation and Entrepreneurship, 2013)
The paper examines family business foundations as connectors between the firm and the family from which they originate, adopting a coevolution approach that considers family and business as two subsystems which coevolve in creating a different species, the family business. Foundations are seen as coevolution facilitators supporting the coevolution process, outlining a specific grow path for family firms, and ensuring family business sustainability. An empirical analysis on Italian family business foundations is developed. The Italian context is taken into consideration because family firms are the backbone of the Italian economy, and the largest family foundations are those created by the most important entrepreneurial families. Data bring to light the structural role played by family business foundations in Italy and their involvement in the field of culture and art, research and training, health care, and territorial responsibility. The analysis shows the growth of family business foundations in recent years and their connection with long-lived companies with whom a close connection is maintained, leading to a lasting intergenerational sustainability.
Keywords: 650; Family business; Foundations; Coevolution process; Sustainability